Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 1312775 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Charadrius veredus Gould, 1848, Podiceps grisegena (Boddaert, 1783), Turdus pilaris Linnaeus, 1758, Pinguinus impennis (Linnaeus, 1758), Aix galericulata (Linnaeus, 1758), Calidris temminckii (Leisler, 1812), Regulus regulus (Linnaeus, 1758), Calidris bairdii (Coues, 1861), Locustella certhiola (Pallas, 1811), Aegolius funereus (Linnaeus, 1758), Charadrius pecuarius Temminck, 1823, Tetraogallus caspius (S.G.Gmelin, 1784), Carpodacus erythrinus (Pallas, 1770), Anser albifrons (Scopoli, 1769), Corvus corax Linnaeus, 1758, Empidonax alnorum Brewster, 1895, Meleagris gallopavo Linnaeus, 1758, Arenaria interpres (Linnaeus, 1758), Tadorna ferruginea (Pallas, 1764), Circaetus gallicus (Gmelin, 1788), Pernis apivorus (Linnaeus, 1758), Charadrius morinellus Linnaeus, 1758, Cathartes aura (Linnaeus, 1758), Sitta krueperi Pelzeln, 1863, Tringa glareola Linnaeus, 1758, Numenius phaeopus (Linnaeus, 1758), Irania gutturalis (Guerin-Meneville, 1843), Anser serrirostris Swinhoe, 1871, Seiurus aurocapilla (Linnaeus, 1766), Marmaronetta angustirostris (Ménétries, 1832), Phylloscopus humei (W.E.Brooks, 1878), Anser erythropus (Linnaeus, 1758), Fringilla montifringilla Linnaeus, 1758, Anas querquedula Linnaeus, 1758, Ptyonoprogne rupestris (Scopoli, 1769), Bulweria bulwerii (Jardine & Selby, 1828), Phylloscopus bonelli (Vieillot, 1819), Branta leucopsis x canadensis, Passer italiae (Vieillot, 1817), Porphyrio martinica (Linnaeus, 1766), Calidris fuscicollis (Vieillot, 1819), Puffinus griseus (Gmelin, 1789), Anser albifrons x caerulescens, Spiza americana (J.F.Gmelin, 1789), Hirundapus caudacutus (Latham, 1802), Calidris ruficollis (Pallas, 1776), Catharus minimus (Lafresnaye, 1848), Actitis hypoleucos (Linnaeus, 1758), Coccothraustes coccothraustes (Linnaeus, 1758), Lophophanes cristatus (Linnaeus, 1758), Larus armenicus Buturlin, 1934, Sylvia undata (Boddaert, 1783), Remiz pendulinus (Linnaeus, 1758), Larus glaucoides B.Meyer, 1822, Pavo cristatus Linnaeus, 1758, Tetrastes bonasia (Linnaeus, 1758), Buteo rufinus (Cretzschmar, 1829), Tyto alba (Scopoli, 1769), Linaria cannabina (Linnaeus, 1758), Puffinus mauretanicus Lowe, 1921)", "Country is Norway", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 1312775 records from 51 constituent datasets: 263 records from iNaturalist Research-grade Observations. 14 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 63 records from Arctic Species Trend Index (ASTI) : Freshwater. 39 records from Geographically tagged INSDC sequences. 1 records from LACM Vertebrate Collection. 22 records from Tetraonid line transect surveys from Norway: Data from Statskog. 22 records from UWBM Ornithology Collection. 31660 records from Norwegian Biodiversity Information Centre - Other datasets. 9 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 6319 records from EBCC Atlas of European Breeding Birds. 483 records from Bird collection NTNU University Museum. 10 records from Collection Ornithologie - SNSD. 9099 records from Birds ringed by Revtangen Bird Observatory 1936-2018, Southwest Norway. 21 records from Macaulay Library Audio and Video Collection. 1 records from Australian National Wildlife Collection provider for OZCAM. 1 records from MVZ Bird Collection (Arctos). 7 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 3 records from Natural History Museum Rotterdam - Specimens. 1216340 records from Norwegian Species Observation Service. 1 records from RBINS DaRWIN. 1113 records from NHMO Bird collection. 995 records from Balsfjord Nature Reserves. 29 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 2 records from E39 Lyngdal - Ålgård. 100 records from Trondheim urban biodyversity survey. 661 records from BioFokus. 6 records from Jordal. 10 records from Paleobiology Database. 2264 records from Observation.org, Nature data from around the World. 3 records from SUI Vertebrate Collection. 1 records from KU E16 Slæn - Tvinno. 900 records from SEAPOP - Last observation per locality in winter season. 235 records from Xeno-canto - Bird sounds from around the world. 1 records from Collections of Bioclass, school #179, Moscow. 1 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 30689 records from EOD - eBird Observation Dataset. 6 records from Museum of Comparative Zoology, Harvard University. 3 records from Population research on small rodents (Rodentia) and screws (Soridae) in Lierne Municipaility – Norway; 1988 – 2017 based on systematic catches with ordinary mouse traps in traplines. 1 records from Tetraonid line transect surveys from Norway: Data from Finnmarkseiendommen (FeFo). 66 records from Sperm morphology of 264 songbird species. 1056 records from Recoveries of birds ringed by Revtangen Bird Observatory (Southwest Norway), 1936-2018. 37 records from International Barcode of Life project (iBOL). 998 records from SEAPOP - Last observation per locality in breeding season. 2 records from University of Michigan Museum of Zoology, Division of Birds. 1 records from Ornithologie Federsammlung - SNSD. 2 records from Lund Museum of Zoology (MZLU). 40 records from Naturalis Biodiversity Center (NL) - Aves. 8420 records from Birds ringed with Norwegian rings 1914-1960. 735 records from naturgucker. 1 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 19 records from Animal Sound Archive. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences